Effects of CYP2C19 Polymorphism on Endothelial Function, Arterial Stiffness and Inflammation in Coronary Artery Disease Patients Under Clopidogrel Treatment - Siasos, Gerasimos; Zaromitidou, Marina; Oikonomou, Evangelos; Mourouzis, Konstantinos; Tsalamandris, Sotiris; Kioufis, Stamatios; Kokkou, Eleni; Vavuranakis, Manolis; Zografos, Theodoros; Antonopoulos, Alexis; Dimitropoulos, Stathis; Stefanadis, Christodoulos; et al. (Current Pharmaceutical Design, 2015)
Background: Clopidogrel’s ability to inhibit platelet function determined its clinical usefulness. The role of CYP2C19*2 genotype on antiplatelet treatment is recently under question. Arterial wall properties and inflammation are key players in atherosclerosis development. Hence, we evaluated the impact of CYP2C19*2 genetic polymorphism on endothelial function, arterial stiffness and inflammation in coronary artery disease (CAD) patients receiving clopidogrel treatment. Methods and Results: In this study we enrolled 408 consecutive patients with stable CAD under dual antiplatelet therapy (clopidogrel 75mg/day, aspirin 100mg/day), 30 days after percutaneous coronary intervention. Measurement of flow-mediated dilation (FMD) of the brachial artery was used to evaluate endothelial function. Carotid-femoral pulse wave velocity (PWV) and augmentation index (AIx) was measured to estimate arterial stiffness. Real time polymerase chain reaction was used for the genotyping of CYP2C19*2. Levels of tumor necrosis factor alpha (TNF-a) and interleukin 6 (IL-6) were measured with ELISA. We found no difference in basic clinical and demographic characteristics nor in FMD, PWV, AIx and inflammatory status (p=NS for all) between CYP2C19 homozygotes for the wild type; carriers of reduced function allele and homozygotes for the reduced function allele. Conclusion: CYP2C19*2 loss of action polymorphism causes no impact on vascular function and inflammatory status in stable CAD patients receiving clopidogrel treatment.
Keywords: atherosclerosis